The Role of Smart Technologies in the Educational Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides a concise overview of the multifaceted role of smart technologies in education. It highlights how these digital tools empower educators, engage students, and promote inclusivity in the learning process. Additionally, it acknowledges challenges such as the digital divide and data privacy concerns while exploring future opportunities, such as AI and immersive technologies, in shaping the future of education.